Dominasi Perempuan dalam Iklan Televisi: Stereotip Gender dalam Iklan Televisi pada SCTV - Auli, Merita; Jamiah, Ririn (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Lampung, 2017)
Advertising becomes a means to meet the information needs for the community. Advertising has also become one of the media that is very effective in attracting the attention and interest of audiences. Advertising becomes a way for producers to reach their target customers. An ad impression is packaged into a form that attracts attention so that the purpose of the product manufacturer can be achieved. One interesting form of ad packaging is to make women as role or role in the ads. This study observed the advertisement that impressions on private television station SCTV for one week with the time of broadcast at 19.00-22.00 WIB. Based on the results of the study found 226 different ads that aired on May 17-24, 2017. It has also done by involving two coding each representing men and women. The results is women have dominance in advertising when compared with men. Women dominate in the role category as much as 33% while men only 17%. While 35% of the locations used are homes and products are widely advertised is food and beverages with the amount of 43%. From the research result, television advertisement in Indonesia has domination of woman with home background and food-beverage product, so women can not escape from stereotype that woman is closely related to taking care of homework, children and family. TV commercials in Indonesia are dominated by women. So that the stereotype of women appear to be one of the decisive indicators of the success of an ad seen from consumer buying interest. Iklan menjadi sarana dalam memenuhi kebutuhan informasi bagi masyarakat. Iklan juga menjadi salah satu media yang sangat efektif dalam menarik perhatian dan minat khalayak. Iklan menjadi salah satu cara bagi para produsen untuk mencapai target konsumennya. Sebuah tayangan iklan dikemas menjadi suatu bentuk yang menarik perhatian sehingga tujuan dari produsen produk dapat tercapai. Salah satu bentuk kemasan iklan yang menarik ialah menjadikan perempuan sebagai role atau pemeran dalam iklan. Penelitian ini mengamati iklan pada stasiun televisi swasta SCTV selama satu minggu dengan waktu tayang pukul 19.00-22.00 WIB. Berdasarkan hasil penelitian ditemukan sebanyak 226 iklan yang berbeda yang tayang pada tanggal 17-24 Mei 2017. Telah dilakukan pula pengkodingan dengan melibatkan dua orang pengkoding yang masing-masing mewakili laki-laki dan perempuan. Hasil pengkodingan menunjukan perempuan memiliki dominasi dalam iklan jika dibandingkan dengan laki-laki. Perempuan mendominasi dalam kategori peran sebanyak 33% sedangkan laki-laki hanyak 17%. Sedangkan 35% lokasi yang digunakan ialah rumah dan produk yang banyak diiklankan ialah makanan dan minuman dengan jumlah 43%. Dari hasil penelitian, iklan televisi di Indonesia memiliki dominasi perempuan dengan latar rumah dan produk makanan-minuman, sehingga perempuan belum bisa lepas dari stereotip bahwa perempuan erat kaitannya dengan mengurus pekerjaan rumah, anak dan keluarga. Iklan televisi di Indonesia didominasi oleh perempuan. sehingga muncul stereotip bahwa perempuan menjadi salah satu indikator penentu dari kesuksesan sebuah iklan dilihat dari minat beli konsumen.